2014
DOI: 10.1080/14772000.2014.892542
|View full text |Cite
|
Sign up to set email alerts
|

Identifying priority conservation areas for the American burying beetle,Nicrophorus americanus(Coleoptera: Silphidae), a habitat generalist

Abstract: Conservation efforts leading to the recovery of the federally endangered American burying beetle (ABB), Nicrophorus americanus Olivier, have been challenging because of the unknown causes of its decline, difficulty in establishing habitat requirements, and unclear population distribution across the species' range. Extant populations of this widespread generalist species occur in broadly separated regions of North America with varying habitat characteristics. A habitat suitability model for ABB in the Nebraska … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 62 publications
1
12
0
Order By: Relevance
“…For semiochemicals other than pheromones, uncertainties of presence or absence have to be adjusted according to the estimated capture probabilities of the respective systems; as stated above, these generally are lower than detection by pheromone-baited traps (Benedick et al 2006; Creighton and Schnell 1998; Jurzenski et al 2014). Unless recapture studies are performed, estimating the true probability of detection for individual species may be difficult, but broad-spectrum captures may still reveal trends for whole communities (Hanski et al 2007).…”
Section: Estimating Change: Distributions and Population Sizesmentioning
confidence: 99%
See 1 more Smart Citation
“…For semiochemicals other than pheromones, uncertainties of presence or absence have to be adjusted according to the estimated capture probabilities of the respective systems; as stated above, these generally are lower than detection by pheromone-baited traps (Benedick et al 2006; Creighton and Schnell 1998; Jurzenski et al 2014). Unless recapture studies are performed, estimating the true probability of detection for individual species may be difficult, but broad-spectrum captures may still reveal trends for whole communities (Hanski et al 2007).…”
Section: Estimating Change: Distributions and Population Sizesmentioning
confidence: 99%
“…As detailed above, however, the difficulty in obtaining accurate data on distribution and abundance could throw these estimates off by a wide margin. Large-scale trapping with pheromones or other semiochemicals provides a standardized way of simultaneously sampling a large number of potential habitats, along broad gradients of differing landscape variables, with considerable accuracy and minimal effort (Gandhi et al 2009; Jurzenski et al 2014; Musa et al 2013; Schroeder 2013). Whereas passive sampling methods rely to a great extent on hotspots or substrate elements where insects aggregate (Brunet and Isacsson 2009), semiochemically-baited traps can be dispersed systematically in the landscape to provide a measure of abundance that is independent of the underlying habitat structure (Benedick et al 2006; Hanski et al 2007; Jurzenski et al 2014; Musa et al 2013).…”
Section: Landscape and Habitat Interactionsmentioning
confidence: 99%
“…Our results suggested that an 800 m radius was appropriate, matching previous estimates of trap sample range (USFWS, ). GIS‐based habitat assessments for N. amerianus have often relied on vegetation maps to assess habitat at appropriate spatial scales (Crawford & Hoagland, ; McPherron et al ., ; Jurzenski et al ., ), but these maps are often only published every 5–10 years (i.e. 5–10 N. americanus generations).…”
Section: Discussionmentioning
confidence: 99%
“…within 100 m of traps), and this may be one factor that has contributed to difficulties detecting habitat associations. There has been some success using GIS to assess N. americanus habitat at larger spatial scales (Crawford & Hoagland, ; McPherron et al ., ; Jurzenski et al ., ), but land cover maps do not account for vegetation dynamics and disturbance histories that may be important for this annual species. Satellite images from Landsat [United States Geological Survey (USGS), ] can be used to measure these vegetation dynamics at large spatial scales.…”
Section: Introductionmentioning
confidence: 99%
“…American burying beetles were listed as federally endangered in 1989 (Federal Register 54[133]: 29652-55). Historical range of the ABB covered much of North America east of the Rocky Mountains; today, however, the ABB is found in isolated populations in only a few states [15].…”
Section: Introductionmentioning
confidence: 99%